Universal, easy access to geotemporal information: FetchClimate. Issue 9 (14th June 2016) - Grechka, Dmitry A.; Berezin, Sergey B.; Emmott, Stephen; Lyutsarev, Vassily; Smith, Matthew J.; Purves, Drew W.
Abstract : Geotemporal information, information associated with geographical space and time, has always been critical to climate and environmental science. However, this information is certainly not universally or easily accessible. In fact, obtaining and using geotemporal information often comes with a considerable technical overheads, impeding research progress. To address this, we introduce FetchClimate: a cloud service designed to provide easy, universal access to geotemporal information. FetchClimate enables and accelerates the use of geotemporal information by enabling it to be accessed programmatically from a Web service (such as the statistical software R) or non‐programmatically using a Web browser. We intend the service to accelerate the pace of ecological and environmental research by eliminating the technical overheads currently needed to obtain geotemporal information. The software, online manual, and user support are freely available at <http://nichea.sourceforge.net >.